The effects of low-fluoride toothpaste supplemented with calcium glycerophosphate on enamel demineralization - Soares Fraga Zaze, Ana Carolina; Dias, Ana Paula [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Springer, 2014)
The aim of the present study was to evaluate the effects of different concentrations of calcium glycerophosphate (CaGP) in toothpastes with low-fluoride (low-F) concentrations on enamel demineralization by using a bovine enamel and pH cycling model.Experimental toothpastes containing 0 or 500 mu g F/g (NaF) and CaGP concentrations of 0, 0.1, 0.25, 0.5, 1, and 2 % were manufactured. A commercial toothpaste was used as a positive control (1,100 mu g F/g). After polishing and hardness tests, enamel blocks were subjected to pH cycling for 5 days and toothpaste treatment twice daily. The treatment regimen involved soaking all blocks in the corresponding slurry for 1 min (2 ml/block). Surface and cross-sectional hardness and fluoride concentrations in enamel were analyzed. The hardness data were analyzed using a one-way ANOVA followed by a Bonferroni post hoc test. Fluoride concentrations were analyzed using a Kruskal-Wallis followed by a Student-Newman-Keuls post hoc test.The mineral loss with the toothpaste containing 500 mu g F/g and 0.25 % CaGP was lower than that in the other groups (p < 0.05). Fluoride concentrations in the enamel treated with 0.1, 0.25, and 0.5 % CaGP toothpastes were similar to those in the enamel treated with the 500 mu g F/g toothpaste (p > 0.05). A greater concentration of CaGP reduced the fluoride levels in enamel (p < 0.05).The results from the present in vitro study show that a low-F (500 mu g F/g) toothpaste is capable of maintaining the efficacy of 1,100 mu g F/g toothpaste when supplemented with 0.25 % of CaGP.The developed toothpaste prevents caries as a standard one and is safe for individuals of any age group.
Keywords: Toothpastes; Fluoride; Polyphosphates; Enamel; Demineralization; In vitro